ChemInform Abstract: Solvent‐Free Mechanochemical Route for Green Synthesis of Pharmaceutically Attractive Phenol‐Hydrazones. Issue 18 (May 2015) - Oliveira, P. F. M.; Baron, M.; Chamayou, A.; Andre‐Barres, C.; Guidetti, B.; Baltas, M.
Abstract Various substituted organic hydrazines and phenol aldehydes efficiently react in a vibratory ball‐mill leading to hydrazones with high level of purity and without the use of any environmentally unadvisable reagents, additives or catalysts.